The use of an integrated marketing communications approach in promoting in the pharmaceutical market - Halchynskyi, Maksym; Syliz, Artem; Polusmiak, Yuliia (Management and Entrepreneurship: Trends of Development, 2024)
Authors of the article explores the impact of marketing communications on the activities of a pharmaceutical company and identifies the leading trends in the use of marketing communication measures in the domestic pharmaceutical market. The relevance of the topic is due to the improvement of the drug promotion system and the use of modern marketing communications for effective management of the pharmaceutical company. It is determined that the pharmaceutical market is quite complex and diverse, with a large number of participants and a list of characteristics that determine the specifics of its functioning and differ significantly from other consumer goods markets. As a result, the marketing strategy and marketing of pharmaceutical products and medicines may differ depending on the type of company. The main characteristics of the pharmaceutical market in modern conditions are investigated. Translated with DeepL.com (free version) Significant tools for drug promotion are separately considered and it is demonstrated that the marketing communications mix (promotion mix) consists of such means of influence as: advertising, sales promotion, personal selling, public relations and the visits of medical representatives. Particular attention is given to the application of the marketing communications mix which allows the company to provide consumers with information about itself and its products, adjust its activities, quickly respond to changes in the market environment, increase sales levels and create a positive image. The research may be useful to managers of pharmaceutical companies, medical representatives, and pharmacists. Results: The study allowed us to identify the leading communication channels in the management of the marketing activities of the pharmaceutical enterprises and to find out their characteristics.JEL Classification: D30, D40, M30, M31, M37